Chapter Jung, Beneduce e i primi anni dell'Iri (1932-1936) - DE IANNI, Nicola (Studi e saggi, 2020)
This essay examines the figures of Jung and Beneduce. From the very beginning of their careers, until the crucial 30's, when the first one was appointed Ministry of Finance and the second one, confidential trustee of Mussolini. For both, the testbed was their work experience at IRI, where they helped create the Italian model of the government intervention in the economy and the nationalisation of the Banca Commerciale Italiana, Credito Italiano e Banco di Roma.